CONTENT ANALYSIS OF COGNITIVE DOMAIN IN SENIOR HIGH SCHOOL ENGLISH TEXTBOOK - Sigiro, Intan; Pelenkahu, Noldy; Rettob, Alloysius (Journal of English Culture, Language, Literature and Education, 2022)
The purpose of this study is to determine the types of cognitive domain in Senior High School English Textbook uses Wh questions based on Revised Bloom s Taxonomy as well as the distribution of higher and lower order thinking skills in Wh questions The descriptive qualitative method uses to perform this investigation The data of this research are Wh questions in Buku Guru Bahasa Inggris for grade 10th Senior High School with 2013 Curiculum published by Kementerian Pendidikan dan Kebudayaan After examining the data the findings of this study reveal that the Wh questions in the textbook did not cover all of the cognitive domains: C1 66 66 C2 33 33 C3 C4 C5 and C6 0 The distribution of low order thinking Remembering C1 28 questions and understanding C2 14 questions include 42 questions 100 There are no issues in the distribution of high order thinking skill such as analyzing evaluating and creating 0 It finds that the ditribution of high and low thinking skills in Wh questions in Buku Guru Bahasa Inggris for grade 10th Senior High School is unbalance < p>